2017
DOI: 10.1371/journal.pone.0187164
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid self-optimized clustering model based on citation links and textual features to detect research topics

Abstract: The challenge of detecting research topics in a specific research field has attracted attention from researchers in the bibliometrics community. In this study, to solve two problems of clustering papers, i.e., the influence of different distributions of citation links and involved textual features on similarity computation, the authors propose a hybrid self-optimized clustering model to detect research topics by extending the hybrid clustering model to identify “core documents”. First, the Amsler network, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
0
18
0
1
Order By: Relevance
“…In recent years, a new class of methods based on network theory have been proposed to analyze texts. Applications of network models in text analysis include the study of scientific documents [5,6,7,8], stylometry [9,10,11,12], sense discrimination [13,14] and several other applications [15,16]. The problem of creating single-document extractive summaries has benefited from these previous network models of texts [17,18,19].…”
mentioning
confidence: 99%
“…In recent years, a new class of methods based on network theory have been proposed to analyze texts. Applications of network models in text analysis include the study of scientific documents [5,6,7,8], stylometry [9,10,11,12], sense discrimination [13,14] and several other applications [15,16]. The problem of creating single-document extractive summaries has benefited from these previous network models of texts [17,18,19].…”
mentioning
confidence: 99%
“…The clusters of DEA concepts identified in this study differ from those of Yu et al (2017). This is not surprising since these researchers use a different methodology:…”
Section: Resultsmentioning
confidence: 66%
“…first clustering papers, not keywords, and then identifying the main DEA topics studied in the papers of each cluster. Yu et al (2017) acknowledge that the clusters they found are mostly related to the applications of DEA in different sectors. Nevertheless, there are certain similarities between the communities shown above and the clusters in Yu et al (2017).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations